1986
DOI: 10.1172/jci112456
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and water balance in chronic congestive heart failure.

Abstract: As the characteristics of sodium and water balance in heart failure remain undefined, we evaluated the hemodynamic, metabolic, and hormonal effects of balanced sodium intake in 10 patients with chronic congestive heart failure. We discontinued diuretics to avoid their confounding influence, and all patients received 1 wk of 10 meq and 100 meq balanced sodium intake and controlled free water. Comparing sodium intake of 10 with 100 meq, the following observations were made. There was weight gain (2.0 kg) and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(71 citation statements)
references
References 35 publications
6
62
1
1
Order By: Relevance
“…In considering the mechanisms responsible for the attenuated response to ANF infusion in heart failure, it should be noted that, under basal conditions, many ofthe patients studied were retaining sodium while on a 100-meq sodium diet. This would be consistent with a previous study by our group (43) demonstrating that only 50% of such patients achieved sodium balance at this level of intake, while the remainder continued to avidly retain sodium. The responsible mechanism could not be identified, but this phenomenon was associated with different patterns of renin-angiotenin system activity.…”
Section: Resultssupporting
confidence: 93%
“…In considering the mechanisms responsible for the attenuated response to ANF infusion in heart failure, it should be noted that, under basal conditions, many ofthe patients studied were retaining sodium while on a 100-meq sodium diet. This would be consistent with a previous study by our group (43) demonstrating that only 50% of such patients achieved sodium balance at this level of intake, while the remainder continued to avidly retain sodium. The responsible mechanism could not be identified, but this phenomenon was associated with different patterns of renin-angiotenin system activity.…”
Section: Resultssupporting
confidence: 93%
“…In these previous studies Low ANP Acute Heart Failure produced by acute inferior thoracic vena caval constriction was characterized by activation of PRA and aldosterone with sodium retention, responses not observed with Elevated ANP Acute Heart Failure produced by rapid ventricular pacing. In chronic severe CHF an escape from the RAAS-suppressing actions of ANP may result in sodium retention (26). Studies in humans and animal models of CHF have demonstrated a blunting of the second messenger cGMP response to endogenous and exogenous ANP in severe CHF, in contrast to a preservation of the second messenger response to acute and chronic endogenous elevation of ANP and exogenous administration of ANP in mild CHF (5,8,27).…”
Section: Discussionmentioning
confidence: 99%
“…Salt restriction should be emphasized, knowing that an increase of daily dietary sodium intake of as little as 10 to 100 mEq results in a 2-kg weight gain and changes in RAAS and SNS activity. 35 350 Clin. Cardiol.…”
Section: Clinical Studies In Heart Failurementioning
confidence: 99%